Socialism and the fishery: a case study of the Cuban shrimp fishery. - Joyce, Ian T. (Canadian Geographer)
The writer investigates whether the problems associated with the exploitation of fish stocks in countries with market economies are to be found in socialist nations. He explores the development of the shrimp fishery in the coastal waters of Cuba in an effort to evaluate the “socialist option” in the exploitation of fish resources. He notes that during the 1960s, Cuba's shrimp fishery was characterized by uncontrolled growth in effort and lack of enforcement of regulations, and by the end of the 1970s, the fishery was beset by problems of biological and economic overfishing typical of shrimp fisheries around the world. He points out that shrimp catches were stabilized in the 1980s, and that Cuba's command economy exhibited some significant advantages over market economies in managing fish stocks. He asserts that the ability of the Cuban state to protect stock, reduce the fishing effort, and ensure alternative employment for shrimp fishers is in stark contrast to the experience of market economies. He notes, however, that the command economy shares with market economies an inability to identify, let alone deal with, long-term environmental change.